Gum Arabic and Eugenol in a Silica-Induced Inflammatory Angiogenesis Model in Wistar Rat - Dutra, Barbara de Araujo Lima; Carneiro, Carolina Lyra Barreira; Melo, Nayanna de Oliveira Ramos; Oliveira, Gilson Brito de; Jamacaru, Francisco Vagnaldo Fechine; Ribeiro, Joao Crispim; Dornelas, Conceição Aparecida (Journal of Pharmacy and Nutrition Sciences, 2022)
This work aims to evaluate the effects of gum arabic and eugenol on inflammatory angiogenesis in a subcutaneous silica inoculum model. Ninety-six Wistar rats were distributed over 16 groups. The substances administered by gavage included distilled water, gum arabic (500 mg/100g weight), and eugenol (10mg/100g weight). Control groups received 0.2 mL of sterile distilled water subcutaneously. The experimental groups were subjected to an inoculum of 0.2 mL of silica solution (50 mg/mL) subcutaneously. For seven or 14 days, the groups received distilled water or gum arabic or eugenol or gum arabic plus eugenol. There was no difference between the histological analysis of slides stained with hematoxylin-eosin. There was a reduction in vascular density in animals that received only gum arabic for 7 (0.09 µm² ± 0.02) or 14 (0.08 µm² ± 0.03) days and only eugenol for seven days (0.08 µm² ± 0.03), but this was not statistically significant. The microvascular density significantly increased in the group treated with eugenol for 14 days (0.14 µm² ± 0.02). Eugenol reduced inflammatory angiogenesis when administered for seven days and stimulated it when administered for 14 days. Gum arabic had a potential inhibitory effect on this model. The study of inflammatory angiogenesis, induced by a silica inoculum in the subcutaneous tissue of rats, is a new and reproducible model for evaluating angiogenesis and inflammation.